Analisis Loss Learning pada Mata Pelajaran PPKN Kelas V Sekolah Dasar - M. Denni Renaldy; Sukardi Sukardi; Murjainah Murjainah (Journal on Education, 2023)
The problem of this research is learning loss during learning, it is known that post-learning which was carried out online previously made student experience learning loss or lost learning concepts, this is evidenced by a decrease in student learning motivation, lack of student discipline and changes in attitudes that are not good for students during learning. The purpose of this study was to describel learning loss in pancasila and citizenship education class V at SD Negeri 07 Palembang. This study used descriptive qualitative method. Data collection techniques used in this study were observation, interviews, test, questionnaires, and documentation. The result of this study on V grade SD Negeri 07 Palembang showed that out of a total of twenty three students, there were nineteen students who experienced learning loss and there were four studenst who did not experience learning loss. In the application of the independent curriculum for civics learning, the results of the tests carried out, namely in the application of the independent curriculum for pancasila and citizenship learning in grade V SD Negeri 07 Palembang showed that the percentage of student scores was greater than the minimum criteria with 78% of students with very high and high criteria, and 22% of students are quite low. Thus it is obtained from the percentage values above, that the problem of learning loss experienced by students is due to the impact of learning carried out online, by implementing an independent curriculum in civics learning can improve and improve academics and attitudes in students.